PERLINDUNGAN HUKUM BAGI PEMEGANG POLIS TERHADAP PERJANJIAN ASURANSI JIWA MENURUT UNDANG – UNDANG NOMOR 40 TAHUN 2014 TENTANG PERASURANSIAN(Studi kasus di PT.Prudential,tbk Cabang Semarang) - Duwi Aryadi; Arga Chon Feriandref, Eka Ermala, Tri Widiastuti, Othman Ballan, Mubaraq (INTELIGENSIA MEDIA, 2024)
Controversy between the policy holder and the insurance company regarding an agreement which is then included in the policy deed has become a serious problem in the insurance business in Indonesia where the rights obtained by the policy holder are not in accordance with what has been agreed. On the other hand, policy holders are generally individuals and quite a few have weak economic conditions. Thus, it is interesting to review juridically regarding legal protection for policy holders against life insurance agreements, the problem formulation is as follows: 1) What is the legal protection for policy holders against life insurance agreements based on Law Number 40 of 2014 concerning insurance; 2) What factors influence legal protection for policy holders regarding life insurance agreements at PT. Prudential life, and how to solve it; 3) How is the dispute resolved between the policy holder and the policy insurer at the insurance company (PT. Prudential, life). This research uses an empirical juridical approach method with analytical descriptive research specifications, the sources and types of data used are primary data and secondary data, and the data analysis used is descriptive qualitative with data collection techniques using library research and field studies. The research location is the Semarang Prudential Insurance branch office located at Jalan Dr. Cipto, Karangturi, East Semarang, Semarang City, Central Java. Based on the research results, it can be seen that: 1) legal protection for life insurance policy holders based on insurance law has been clearly regulated in article 53 and article 54 of Law Number 40 of 2014 concerning insurance. Legal protection for policy holders is not limited to insurance law, but is also protected by OJK regulation Number 1/POJK.07/2013 in article 1 paragraph 1, article 4 and article 7. As is the duty and authority of the OJK as an instrument to supervise and limiting insurance companies in their abuse of policy holders. 2) the most dominant factor influencing legal protection for policy holders is the factor of insurers and insurance agents in providing services and granting claims which are often seen by insureds as complicated in their procedures. 3) dispute resolution of claims rejection by the insurer is more likely to be resolved through mediation as mandated in article 54 of the insurance law (paragraphs 1-4) as an example of the case in the name of Hotmauli Manurung with the company PT. Prudential, life.